Ekosistem Pendidikan dalam Perspektif Al-Qur’an - Abdul Rokhim; Ahmad Zain Sarnoto; Ahmad Thib Raya; Samsul Bahri (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This paper aims to show the importance of the Al-Qur'an perspective education ecosystem in improving the quality of education. The method used is phenomenological qualitative, with a literature approach. This study shows that the Qur'anic perspective on the educational ecosystem is found in five signs, namely, ta'ȃwun, takȃful, syirkah, al-jauz, and ukhuwah. The metaphor of reciprocal relationships in the explanation of these terms can be used as a sign of cooperation in the world of education known as the educational ecosystem. The mutualistic cooperation in question is between components or educational institutions, namely the family environment, schools, communities, mosques, social media, work environments, and the natural environment. The synergy between these educational institutions will ensure an increase in the quality of education.